BIMBINGAN DAN PELATIHAN IMPLEMENTASI KEPEMIMPINAN UNTUK PEMBERDAYAAN IBU-IBU PKK RW 03 KELURAHAN KETAWANG GEDE KOTA MALANG - Masreviastuti; Mahmudatul Himmah; Helmy Adisaksana; Lilies Nur Aini; Fauziah (Jurnal Pengabdian Polinema Kepada Masyarakat, 2021)
To create harmonious living conditions, group members must respect and appreciate each other. Humans are endowed with the ability to think, the ability to sort & choose what is good & what is bad. With these advantages, humans should be able to manage the environment well. Not only should the environment be managed properly, human social life also needs to be managed properly. For that we need quality human resources. A resource with a leadership spirit, at least to lead himself. In RW 03, Ketawang Gede Village, the number of PKK members consists of 30 mothers with 90% professions: entrepreneurs, 10% private employees and civil servants aged between 25 - 50 years where they always need to do independent and team work. With the spirit of a human leader, he will be able to manage himself, the group & the environment well. Especially in dealing with problems that are relatively complicated & difficult, so a leader is required to be wise in making decisions so that problems can be resolved properly.